Evaluation of Agronomic and Genetic Diversity in M2V1 Generation of Marigold (Tagetes erecta L.) - Nabilah, Noorfakhriyah Ahsanti; Aisyah, Syarifah Iis; Muhamad Syukur; Dewi Sukma (Journal of Tropical Crop Science, 2024)
Marigold (Tagetes erecta L.) is an ornamental plant widely used as a potted or cut flower due to its vibrant colors and diverse flower shapes. High genetic diversity is essential for successful breeding programs aimed at developing superior varieties. Genetic information can be obtained by estimating variance components and heritability values, key parameters in plant breeding. A high heritability value suggests that genetic factors influence a plant's characteristics more than environmental factors. This study assessed the genetic diversity and performance of vegetative propagation from 2nd generation mutant plants (M2V1). The research was conducted at the Pasir Sarongge experimental field in Cianjur Regency from July to October 2023, using a randomized complete block design with 17 genotypes and three replicates. The genotypes included 14 from vegetative propagation of M2V1 mutant plants and three comparison varieties: “Maharani”, “BAIP 2”, and “BAIP 3”. Data analysis was performed using PKBT-STAT 3.1 software, followed by the honest significant difference (HSD) test at the 5% level. The results revealed significant differences among genotypes in plant height, stem diameter, canopy width, leaf width, flower weight, flower diameter, number of flowers per plant, total flower weight per plant, and flower stalk length. Floret types observed were either all ligulate or all tubuligulate, with flower colors ranging from orange to yellow to white. Traits such as canopy width, flower weight, flower diameter, and stalk length, which exhibited broad genetic diversity and high heritability, can be used for selection in future marigold breeding programs.